Cooperation Employee Performance: The Effect Factors and Implication - Quraisy, Ahmad; Syifa Fatimah, Thalita; Millah Irsyaddin, Muhammad (Greenation International Journal of Law and Social Sciences, 2023)
In this investigation, we aimed to analyze how leadership and compensation influence motivation and ultimately impact the job performance of Cooperation in Padang. To achieve this goal, we utilized a descriptive-verificative research approach through surveys completed by 330 Cooperation employees. Our data was analyzed using the Linear Structural Relationship (LISREL) 8.80 program that employed the Structural Equation Model (SEM). The findings of this study revealed that both compensation and leadership positively contribute to motivation, which in return, plays a critical role in advancing employee performance. Significantly, both compensation and leadership, along with motivation, were found to have a considerable positive effect on staff members' performance. The motivation variable came out on top as the most dominant influence on performance, with compensation leading the way as the most influential variable on motivation. The findings suggest that to enhance employee performance in the Cooperation in Padang district, there needs to be a focus on nurturing employee motivation in the Cooperation in Padang regency. This can be achieved by placing importance on developing strong relationships with members and co-workers, which was highlighted as the key factor in boosting motivation levels. As a result of this research, managers should consider prioritizing strategies that foster healthy work relationships to improve overall performance.